HRAS‐driven cancer cells are vulnerable to TRPML1 inhibition. (20th February 2019) - Jung, Jewon; Cho, Kwang‐Jin; Naji, Ali K; Clemons, Kristen N; Wong, Ching On; Villanueva, Mariana; Gregory, Steven; Karagas, Nicholas E; Tan, Lingxiao; Liang, Hong; Rousseau, Morgan A; Tomasevich, Kelly M; et al.
Abstract: By serving as intermediaries between cellular metabolism and the bioenergetic demands of proliferation, endolysosomes allow cancer cells to thrive under normally detrimental conditions. Here, we show that an endolysosomal TRP channel, TRPML1, is necessary for the proliferation of cancer cells that bear activating mutations in HRAS . Expression of MCOLN1, which encodes TRPML1, is significantly elevated in HRAS ‐positive tumors and inversely correlated with patient prognosis. Concordantly, MCOLN1 knockdown or TRPML1 inhibition selectively reduces the proliferation of cancer cells that express oncogenic, but not wild‐type, HRAS . Mechanistically, TRPML1 maintains oncogenic HRAS in signaling‐competent nanoclusters at the plasma membrane by mediating cholesterol de‐esterification and transport. TRPML1 inhibition disrupts the distribution and levels of cholesterol and thereby attenuates HRAS nanoclustering and plasma membrane abundance, ERK phosphorylation, and cell proliferation. These findings reveal a selective vulnerability of HRAS ‐driven cancers to TRPML1 inhibition, which may be leveraged as an actionable therapeutic strategy. Synopsis: Tumors with oncogenic HRAS mutations upregulate endolysosomal biogenesis. Depletion or inhibition of the TRP channel TRPML1 attenuates proliferation of cancer cells, revealing a selective vulnerability of HRAS ‐driven cancers to TRPML1 inhibition. Cancers with oncogenic HRAS mutations show increased endolysosomal transcription. MCOLN1, which encodes the TRP channel TRPML1, is significantly elevated in HRAS ‐positive tumors. Depletion of MCOLN1, or inhibition of TRPML1, reduces the proliferation of HRAS ‐mutant cancer cells. TRPML1 maintains oncogenic HRAS at the plasma membrane by regulating cholesterol homeostasis. Abstract : Tumors with oncogenic HRAS mutations upregulate endolysosomal biogenesis. Depletion or inhibition of the TRP channel TRPML1 attenuates proliferation of cancer cells, revealing a selective vulnerability of HRAS ‐driven cancers to TRPML1 inhibition.